2010
DOI: 10.1080/10476210903518396
|View full text |Cite
|
Sign up to set email alerts
|

Triad dynamics: investigating social forces, roles, and storylines

Abstract: This is a phenomenological study of the relationships between university supervisors, in-service and pre-service teachers (triads). Two triads participated in a joint pre-service and in-service professional development project. Multiple indepth interviews were completed with each triad member to better record and resolve the varied experiences of the participants. Through using positioning theory as a lens for interpreting data, triad dynamics were explicated to understand relationships within these groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Clarke et al (2014) salientam a importância de se manter uma relação estreita entre estas duas entidades, a faculdade e a escola e, especialmente, entre os seus protagonistas, OF e PC. Outros estudos colocam ênfase na relação que se estabelece entre os elementos da tríade PC -EE -OF (Bradbury & Koballa Jr, 2008;Bullough & Draper, 2004;Campbell, Lott, & Campbell, 2010;Graham, 2006), dando conta da influência desta relação sobre a aprendizagem e o desenvolvimento profissional do EE e, em especial, da importância de manter um diálogo aberto e uma comunicação regular e frutífera durante o processo de estágio. Beck e Kosnik (2002) defendem que a faculdade, em geral, e o OF, em particular, se devem envolver, apoiando o PC no acompanhamento do processo de estágio na escola.…”
Section: Introductionunclassified
“…Clarke et al (2014) salientam a importância de se manter uma relação estreita entre estas duas entidades, a faculdade e a escola e, especialmente, entre os seus protagonistas, OF e PC. Outros estudos colocam ênfase na relação que se estabelece entre os elementos da tríade PC -EE -OF (Bradbury & Koballa Jr, 2008;Bullough & Draper, 2004;Campbell, Lott, & Campbell, 2010;Graham, 2006), dando conta da influência desta relação sobre a aprendizagem e o desenvolvimento profissional do EE e, em especial, da importância de manter um diálogo aberto e uma comunicação regular e frutífera durante o processo de estágio. Beck e Kosnik (2002) defendem que a faculdade, em geral, e o OF, em particular, se devem envolver, apoiando o PC no acompanhamento do processo de estágio na escola.…”
Section: Introductionunclassified
“…Otherwise, as stated by Lesain-Delabarre (1998), the equality or inequality of each person's contributions is more or less defined by the specific context of the relationship and by the pursuit of different objectives even while seeking common goals. Other authors (Campbell & Lott, 2010;Gervais, 2008;Ferrier-Kerr, 2009) claim that the status of individuals in interaction does not determine the quality of their collaboration. Even if the Brock Education Journal, 26(1), 2016 collaborative dialogue is materialized more readily in an egalitarian context, a professional relationship characterized by collaboration is also possible in an asymmetric professional relationship (Portelance, 2011).…”
Section: Interprofessional Collaborationmentioning
confidence: 99%
“…In the same vein, Van Zee, Lay & Roberts (2003) found that the role of the cooperating teacher within the triad is secondary. Nevertheless, according to the findings of Campbell & Lott (2010), despite the constraints of an apparent lack of parity, it is possible to create within the triad an environment of collaboration that promotes professional development. Similar claims by Ofstedal & Dahlberg (2009) indicate that communication skills are a valuable resource.…”
Section: Interprofessional Collaborationmentioning
confidence: 99%
See 2 more Smart Citations